Factors affecting China smartphone brand preference among millennials / Nur Izyan Alyani Abg Ali - Abg Ali, Nur Izyan Alyani (Faculty of Business and Management, 2019)
In this globalization era, smartphone has become as a necessity to a person. The demand and the usage of smartphone has increase year by year. There are many smartphone brands in the market. However, China brand manage to conquer the smartphone market by holding one fourth of the market share. The purpose of this study is to identify what are the factors that influence china smartphone brand preference among millennials. In this study, the researcher stated that price, feature and appearance are the factors that influence China smartphone brand preference among millennials. This research is a qualitative research which had used the questionnaires as the instrument for the collection of data. The data was collected through Google Form from 267 respondents. However, only 90 respondents fulfilled the requirement of this study. Sampling technique that has been used in this study was convenience sampling method. The data collected was then evaluated by using Statistical Package of the Social Science (SPSS) Version 22 Software. Numerous tests were run such as reliability test, frequency distribution, descriptive analysis Pearson’s correlation analysis and multiple regressions. The results indicated that price has a significant relationship with China smartphone brand preference. Besides, the finding shows that feature has a significant relationship with China smartphone brand preference. Also, the study shows that appearance has a significant relationship with China smartphone brand preference. The recommendations stated in this study are to improve feature of smartphone, improve the appearance also reduce price of the smartphone